2014
DOI: 10.1002/ajh.23812
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 dose escalation study of idarubicin combined with methotrexate, vindesine, and prednisolone for untreated elderly patients with primary central nervous system lymphoma: The GOELAMS LCP 99 trial

Abstract: Treatment of primary central nervous system lymphoma (PCNSL) in elderly patients remains unsatisfactory. To develop a new high-dose methotrexate (HD-MTX)-based regimen including idarubicin, a phase 1 multicenter dose escalation study was conducted to determine the maximum-tolerated dose (MTD) of idarubicin. Thirty-five immunocompetent patients with PCNSL were enrolled. The median age was 65 years (range, 60-70 years). MTX and vindesine (VDS) were given at the fixed dose of 3 g/m 2 (6-hr intravenous [IV]) and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Based on a recent systematic review, 7 only few prospective multicentre studies focussing on elderly patients with PCNSL have been reported, 14, 15, 16, 17, 18, 19, 20 which all used HD-MTX-based chemotherapy. However, no standard protocol has yet been defined and there was no study that used rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent systematic review, 7 only few prospective multicentre studies focussing on elderly patients with PCNSL have been reported, 14, 15, 16, 17, 18, 19, 20 which all used HD-MTX-based chemotherapy. However, no standard protocol has yet been defined and there was no study that used rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Unfortunately, this recommendation was not supported by other clinical trials. [ 30 , 35 , 36 ] Thus, in the current study, we used a median IDA dose of 8.5mg/m 2 . Further studies are needed to establish the standard dosage for IDA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent systematic review, 9 a limited number of prospective multicentre studies focussing on elderly PCNSL patients has been reported. 8,[17][18][19][20][21] Most of the studies included HD-MTX in combination with partner chemotherapy agents, but to-date no standard protocol has been defined. Acknowledging the limitations of intertrial comparison, the best reported response rate was 79% but the corresponding 1-year PFS was only 36%.…”
Section: Strengths and Limitationsmentioning
confidence: 99%